Porous Materials: Neuroprotective Effect of Nerve Growth Factor Loaded in Porous Silicon Nanostructures in an Alzheimer's Disease Model and Potential Delivery to the Brain (Small 45/2019). Issue 45 (6th November 2019) - Zilony‐Hanin, Neta; Rosenberg, Michal; Richman, Michal; Yehuda, Ronen; Schori, Hadas; Motiei, Menachem; Rahimipour, Shai; Groisman, Alexander; Segal, Ester; Shefi, Orit
Abstract : In article number 1904203, Ester Segal, Orit Shefi, and co‐workers safely implant or biolistically introduce degradable porous silicon carriers into the brains of mice for continuous and effective release of nerve growth factor, a neuroprotective drug for Alzheimer's disease.